Effect of static magnetic field on endospore germination. Issue 2 (10th November 2016) - Wu, Wen Jie; Liu, Si Li; Yung, Pun To
Abstract : This work investigated the effect of static magnetic field (SMF) on Bacillus atrophaeus endospore germination. Germination was triggered by L‐alanine in 1.3‐T SMF and characterized by ion release, Ca 2+ ‐dipicolinic acid release, and water influx. These events were monitored by electrical conductivity, Tb‐DPA fluorescence, and optical density, respectively. Culturability of endospore germinated in SMF exposure was evaluated by CFU enumeration. Results indicated that 1.3‐T SMF failed to significantly affect endospore germination and culturability, suggesting that the three aforementioned processes were not sensitive to SMF. Bioelectromagnetics. 38:121–127, 2017. © 2016 Wiley Periodicals, Inc.